Analisis Manajemen Kelas guru geografi di SMA Kampar Timur - Ardiyansah; Addina Zaharah; Ibnu Thayibur Rizqi; Nila Armita; Ade Irma (RUBINSTEIN, 2026)
This study aims to analyze in depth the implementation of classroom management in Geography learning at public senior high schools in East Kampar to support effective and conducive learning processes. This research employed a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation. The findings indicate that Geography teachers implemented classroom management through structured lesson planning, flexible classroom arrangement, and the creation of a learning climate that encouraged students’ active participation. Positive interpersonal communication between teachers and students also played an important role in maintaining discipline and minimizing disruptions during instruction. Other findings show that classroom management directly improved learning motivation, discussion engagement, and students’ ability to understand Geography concepts contextually, although challenges remained, including differences in student characteristics and limited learning facilities. The theoretical and practical implications of this study strengthen the view that classroom management is an integral component of pedagogical strategy in Geography education. Practically, the findings may serve as a reference for teachers and schools in designing adaptive, effective, learner-centered management models. The study concludes that consistent classroom management improves Geography learning quality and outcomes.